Preparation and application of a modified ultra-thin cellulose membrane

By using functional group cellulose and functional materials to modify the ultra-thin cellulose separator, the problem of zinc dendrites growth in aqueous zinc-based energy storage systems is solved, and a longer service life and broader application prospects are achieved.

CN114744367BActive Publication Date: 2025-02-18JINAN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210457721.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-28
Publication Date
2025-02-18
Estimated Expiration
2042-04-28

AI Technical Summary

Technical Problem

The aqueous zinc-based energy storage system is prone to zinc dendrites to grow during repeated charging and discharge, resulting in short circuits in the device, limiting its service life and large-scale application.

Method used

Cellulose containing functional groups is used as the separator matrix to inhibit the anion migration of the electrolyte by functional groups, increase the number of zinc ions migration, and introduce functional materials to enhance the puncture strength of the separator and regulate the deposition behavior of zinc ions, and inhibit the growth of zinc dendrites. .

Benefits of technology

It has achieved effective inhibition of zinc dendrites, extended the service life of the aqueous zinc-based energy storage system, and promoted its large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114744367B_ABST
    Figure CN114744367B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electrochemical energy storage, and discloses the preparation and application of a modified ultra-thin cellulose diaphragm. The present invention adopts a vacuum filtration method to directly filter cellulose or cellulose modified by functional materials onto a filter membrane substrate, and peels off the filter membrane substrate after drying to construct a modified ultra-thin cellulose diaphragm. The modified ultra-thin cellulose diaphragm has the functions of high puncture strength, promoting the homogenization of the electric field and ion field on the surface of the zinc negative electrode during zinc ion deposition, optimizing the orientation of the zinc deposition crystal plane, and reducing the nucleation barrier, so as to achieve the effect of inhibiting the growth of zinc dendrites. Thereby realizing a high-stability, long-cycle-life aqueous zinc-based energy storage system, which is of great significance to promoting the practical application of aqueous zinc-based energy storage systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage, and particularly relates to the preparation and application of a modified ultra-thin cellulose diaphragm. Background Art

[0002] The rapid development of human society is accompanied by the huge consumption of fossil fuels and the environmental pollution caused by their combustion. Therefore, electrochemical energy storage devices with advantages such as high energy storage / conversion efficiency and green environmental protection have been increasingly studied. Aqueous batteries have higher safety performance and lower cost because they use aqueous solutions of metal salts as electrolytes; and the ionic conductivity of aqueous solutions of metal salts as electrolytes is much higher than that of organic electrolytes used in lithium-ion batteries, so aqueous batteries have broad application prospects in the field of energy storage and are considered to be battery systems suitable for large-scale and cheap energy storage. Among them, aqueous zinc-based energy storage systems (including aqueous zinc-ion batteries and zinc-ion hybrid capacitors) have become a research hotspot in the field of electrochemical energy storage in recent years due to their advantages such as high safety, abundant raw materials, low price, and environmental friendliness. Aqueous zinc-based energy storage systems usually use metallic zinc as the negative electrode, and their high theoretical specific capacity (820mAh / g) and low redox potential (-0.762V vs. standard hydrogen electrode) are conducive to improving the battery energy density. However, in practical applications, one of the main problems faced by aqueous zinc-based energy storage systems is the zinc dendrite problem. The zinc ions dissolved from the zinc metal surface during the discharge process will be redeposited on the zinc metal negative electrode during the charging process. Due to the tip effect of the uneven surface of the zinc metal, the uneven deposition of zinc ions during repeated charging and discharging causes the growth of zinc dendrites, resulting in device short circuit, which limits the service life and large-scale application of aqueous zinc-based energy storage systems with metallic zinc as the negative electrode. Therefore, solving the problem of zinc dendrites has always been the core issue in the study of zinc negative electrodes. One of the solutions is to develop a diaphragm that can inhibit the growth of zinc dendrites. Because cellulose contains a large number of hydrogen bonds, it can self-assemble into a film in a dehydrated state with the help of hydrogen bonds, van der Waals forces or electrostatic forces. Compared with commercial glass fiber diaphragms, cellulose diaphragms have the advantages of low cost, renewability, high mechanical properties, and good hydrophilicity, and can be used as a diaphragm matrix material for inhibiting zinc dendrites. However, for example, the cellulose diaphragm prepared by the solution casting method has limited effect on inhibiting zinc dendrites. At 5mA / cm 2 、2.5mAh / cm 2Under the conditions of , the cycle life of the symmetrical battery assembled based on it is only 20 hours (Nano Energy, 2021, 89, 106322). In addition, in order to ensure its inhibitory effect on zinc dendrites, the thickness of the cellulose diaphragm using the prior art is often unable to achieve ultra-thinness. For example, in the Chinese patent publication CN 112332026 A, a cellulose-based diaphragm prepared by a coating method, the preferred cellulose diaphragm has a thickness of 100 μm; the thickness of the cellulose diaphragm prepared by Zhou et al. is 140 μm (Energy Storage Materials, 2022, 44, 57-65). As one of the key components in aqueous zinc-based energy storage devices, the use of thick diaphragms significantly reduces the specific energy (including volume specific energy and mass specific energy) of the aqueous zinc-based energy storage system, and at the same time leads to an extension of the electrolyte ion transmission distance during the charge and discharge process, which is not conducive to achieving fast charge and discharge and high power density, and hinders its industrial application. For example, the thickness of commercial lithium-ion battery diaphragms currently does not generally exceed 25 μm. Summary of the invention

[0003] In view of the shortcomings of the existing aqueous zinc-based energy storage system diaphragm materials, the purpose of the present invention is to provide a method for preparing a modified ultra-thin cellulose diaphragm. The present invention selects cellulose containing functional groups as the diaphragm matrix material, utilizes the inhibitory effect of functional groups on the migration of electrolyte anions, increases the number of zinc ion migration, and reduces the local spatial charge accumulation on the surface of zinc metal, and finally inhibits the growth of zinc dendrites; further, by introducing functional materials to modify the cellulose diaphragm matrix, under the premise of ensuring the preparation of ultra-thin cellulose diaphragms, by selecting different functional materials to enhance the puncture strength of the cellulose diaphragm matrix, regulate the electric field and ion field distribution of the negative electrode surface during zinc ion deposition, crystal plane orientation, reduce the nucleation barrier, etc. to optimize the zinc ion deposition behavior, achieve the effect of effectively inhibiting zinc dendrites, extend the service life of the aqueous zinc-based energy storage system, and promote its large-scale application.

[0004] Another object of the present invention is to provide a modified ultra-thin cellulose separator prepared by the above method.

[0005] Another object of the present invention is to provide an application of a modified ultra-thin cellulose membrane, the application object of which is an aqueous zinc-based energy storage system.

[0006] The purpose of the present invention is achieved through the following solutions:

[0007] A method for preparing a modified ultrathin cellulose separator comprises the following steps:

[0008] (1) uniformly dispersing cellulose nanofibers in water to obtain a cellulose aqueous suspension; dispersing the functional material in a solvent to obtain a suspension 2;

[0009] (2) This step is the following step (2.1) or step (2.2):

[0010] (2.1) blending the aqueous cellulose suspension and the suspension 2, and then filtering the mixture onto a filter membrane substrate. After drying at room temperature, the filter membrane substrate is peeled off to obtain a modified ultrathin cellulose membrane.

[0011] Alternatively, (2.2) the aqueous cellulose suspension is filtered onto a filter membrane substrate to obtain an ultrathin cellulose membrane matrix, and then the suspension 2 is immediately filtered onto the ultrathin cellulose membrane matrix to obtain a modified ultrathin cellulose membrane.

[0012] Considering that the separator plays the role of transmitting ions and preventing electrons from passing through, in order to prevent the introduction of the conductive functional layer from causing a battery short circuit, the step (2.2) is particularly suitable for the functional material being a conductive material. When the modified ultra-thin cellulose separator whose functional material is a conductive material is prepared by the step (2.2), when used in a zinc-zinc symmetrical battery, two modified ultra-thin cellulose separators need to be stacked to avoid causing a battery short circuit, and the surface functional layer side of the two modified ultra-thin cellulose separators faces the two zinc foils respectively.

[0013] The cellulose nanofibers described in step (1) are cellulose nanofibers having hydroxyl, carboxyl or amino functional groups on the surface, with a diameter of 5-200 nm and a length of 0.5-20 μm;

[0014] The concentration of the cellulose dispersion in step (1) is 0.5-1 mg / mL so that the cellulose nanofibers can be fully dispersed.

[0015] The functional material described in step (1) includes at least one of zirconium hydrogen phosphate nanosheets, silicon dioxide nanofibers, nano zinc oxide, nano aluminum oxide, halloysite nanotubes, nano tin, copper nanowires, copper / carbon composites, candle ash, cellulose nanofiber-derived carbon, barium titanate, strontium titanate, barium strontium titanate, bismuth titanate, lead titanate, lead zirconate, sodium bismuth titanate, barium strontium titanate, cadmium niobate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, and polyethylene oxide;

[0016] The solvent used to disperse the functional material in step (1) is one of water, an organic solvent or a water / organic solvent mixture;

[0017] The amounts of the functional material and the solvent in step (1) satisfy: the concentration of the functional material in the solvent is 0.05-10 mg / mL, preferably 0.1-3 mg / mL;

[0018] The amount of the cellulose aqueous suspension and the suspension 2 in step (2.1) and step (2.2) is such that the loading amount of the cellulose nanofibers is 0.5-10 mg / cm2 , preferably 1-6 mg / cm 2 The loading amount of the functional material is 0.1-9 mg / cm 2 , preferably 0.3-5 mg / cm 2 The mass fraction of the functional material in the modified ultra-thin cellulose membrane is 0-90%, preferably 5%-50%. The loading amount refers to the loading amount relative to the filter membrane substrate, such as the cellulose loading amount is 1 mg / cm 2 The membrane is used to filter 12.56 mg of cellulose to a load area of ​​12.56 cm 2 on the filter membrane.

[0019] Preferably, in step (2.2), for the surface functional layer material that is easy to fall off, in order to ensure the film-forming quality of the surface functional layer, a certain proportion of cellulose nanofibers is often mixed into the suspension 2 in step (2.2), which mainly acts as a binder. The mass percentage of the mixed cellulose nanofibers in the functional material is 0-20%.

[0020] The filter membrane substrate described in step (2.1) and step (2.2) is a mixed cellulose water filter membrane (applicable to functional materials using water as solvent) or a nylon filter membrane (applicable to functional materials using organic solvents or water or a mixture of the two as solvents), with a pore size of 0.01-2 μm;

[0021] A modified ultra-thin cellulose membrane prepared by the above method, wherein the thickness of the modified ultra-thin cellulose membrane is 3-80 μm, preferably 5-40 μm.

[0022] The modified ultra-thin cellulose membrane of the present invention uses cellulose nanofibers containing functional groups as the membrane matrix, and has the characteristics of ultra-thinness, puncture resistance, high liquid retention and high porosity, and the cellulose membrane is modified by introducing functional materials (including zirconium hydrogen phosphate nanosheets, silicon dioxide nanofibers, nano zinc oxide, nano alumina, halloysite nanotubes, nano tin, copper nanowires, copper / carbon composite materials, candle ash, cellulose nanofiber derived carbon, barium titanate, strontium titanate, barium strontium titanate, bismuth titanate, lead titanate, lead zirconate, sodium bismuth titanate, barium strontium titanate, cadmium niobate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyethylene oxide). It is of great significance to promote the practical application of aqueous zinc-based energy storage systems.

[0023] An aqueous zinc-based energy storage system comprises the modified ultra-thin cellulose diaphragm.

[0024] The mechanism of the present invention is as follows:

[0025] The functions of the functional materials selected in the present invention are as follows: (1) Inorganic reinforcing phases such as zirconium hydrogen phosphate nanosheets, silicon dioxide nanofibers, nano zinc oxide, and nano aluminum oxide are used to improve the puncture strength of the diaphragm to mechanically inhibit the growth of zinc dendrites; (2) Halloysite nanotubes with ion screening function are used to regulate the selective deposition path of anions and cations in the electrolyte to limit the movement of anions and increase the number of zinc ion migration, thereby weakening the phenomenon of zinc dendrite formation induced by the local space charge effect on the surface of the zinc negative electrode; (3) Conductive zinc-philic materials such as nano-tin, copper nanowires, copper / carbon composites, candle ash, and cellulose nanofiber-derived carbon are used to reduce the zinc ion nucleation barrier and accelerate the formation of zinc dendrites. Its deposition kinetics reduces the local current density on the surface of the zinc negative electrode, promotes the homogenization of the electric field, and makes the zinc ions deposited evenly; (4) using barium titanate, strontium titanate, barium strontium titanate, bismuth titanate, lead titanate, lead zirconate, sodium bismuth titanate, barium strontium titanate, cadmium niobate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, and polyethylene oxide materials with high dielectric constants, and utilizing their Maxwell-Wagner polarization effect under an external electric field to regulate the ion transport path on the surface of the zinc negative electrode, accelerate the zinc ion transport, and at the same time repel anions to inhibit the formation of by-products such as basic zinc sulfate, thereby promoting the uniform deposition of zinc, inhibiting the growth of zinc dendrites, and improving the cycle stability of the zinc negative electrode.

[0026] From the perspective of practical application, the present invention designs and prepares an ultra-thin cellulose membrane for an aqueous zinc-based energy storage system, thereby improving the specific energy of the aqueous zinc-based energy storage system and reducing its production cost; by introducing a cellulose membrane functional material layer, the functional material and cellulose are directly mixed to form a film; or an independent functional layer is introduced to regulate the electric field / ion field and nucleation barrier of zinc ions during the charging and discharging process, ultimately achieving uniform deposition of zinc ions on the zinc metal surface, inhibiting the growth of zinc dendrites, and increasing its cycle life.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) The modified ultra-thin cellulose membrane constructed by the present invention selects different functional materials to enhance the puncture strength of the cellulose membrane matrix, promotes the homogenization of the electric field and ion field on the surface of the zinc negative electrode during zinc ion deposition, optimizes the orientation of the zinc deposition crystal plane, reduces the nucleation barrier, and other methods to regulate the zinc ion deposition behavior, thereby realizing a high-stability, long-cycle-life aqueous zinc-based energy storage system;

[0029] (2) Compared with the reported diaphragms for aqueous zinc-based energy storage systems and the existing technologies for inhibiting the formation of zinc dendrites, the modified ultra-thin cellulose diaphragm of the present invention has a simple preparation method, low cost, good effect, and is suitable for large-scale production and practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1The loading capacity for the preparation is 3 mg / cm 2 Thickness cross-section diagram of ultra-thin cellulose separator;

[0031] Figure 2 The loading capacity for the preparation is 3 mg / cm 2 Surface morphology of ultrathin cellulose membrane;

[0032] Figure 3 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 When using the loading amount of 1, 3, 9 mg / cm 2 Constant current charge-discharge curves of the zinc-zinc symmetric battery with ultrathin cellulose separator;

[0033] Figure 4 At a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 When using the loading amount of 1, 3, 9 mg / cm 2 Constant current charge-discharge curves of the zinc-zinc symmetric battery with ultrathin cellulose separator;

[0034] Figure 5 At a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 When the constant current charge and discharge curve of the zinc-zinc symmetric battery using nano-zinc oxide modified ultra-thin cellulose separator;

[0035] Figure 6 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 and a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 When , the constant current charge-discharge curves of the zinc-zinc symmetric battery using the ultrathin cellulose separator modified with halloysite nanotubes;

[0036] Figure 7 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 and a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 When the surface functional layer of copper nanowires is used to modify the ultra-thin cellulose membrane, the constant current charge-discharge curve of the zinc-zinc symmetric battery;

[0037] Figure 8 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm2 and a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 When the surface functional layer of copper / carbon composite material is used to modify the ultra-thin cellulose separator, the constant current charge-discharge curve of the zinc-zinc symmetric battery;

[0038] Fig. 9 At a current density of 5 mA / cm 2 , cut-off capacity is 2.5mAh / cm 2 Galvanostatic charge-discharge curves of a zinc-zinc symmetric battery using an ultrathin cellulose separator modified with a cellulose nanofiber-derived carbon surface functional layer;

[0039] Fig.10 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 When the constant current charge and discharge curve of the zinc-zinc symmetric battery using nano-barium titanate modified ultra-thin cellulose separator;

[0040] Fig.11 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 When , the constant current charge and discharge curve of the zinc-zinc symmetric battery using non-woven fabric separator;

[0041] Fig.12 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 Galvanostatic charge-discharge curves of a zinc-zinc symmetric battery using a commercial cellulose paper separator.

[0042] Fig.13 At a current density of 1 mA / cm 2 , cut-off capacity is 0.5mAh / cm 2 Galvanostatic charge-discharge curves of a Zn-Zn symmetric cell using a commercial glass fiber separator. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0044] Example 1

[0045] Preparation of ultrathin cellulose membrane

[0046] (1) Commercial hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) weighing 12.6, 37.7, and 113.1 mg respectively were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL, and the dispersion was evenly dispersed by ultrasound. The above dispersion was filtered onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain hydroxycellulose nanofibers with loadings of 1, 3, and 9 mg / cm 2 Ultrathin cellulose membrane with a loading of 3 mg / cm 2 The thickness of the ultra-thin cellulose membrane is about 16 μm, and the thickness cross-section diagram is shown in Figure 1 shown. Figure 2 The loading amount is 3 mg / cm 2 The surface morphology of the ultra-thin cellulose membrane. From the figure, we can see that the ultra-thin cellulose membrane is made of cellulose nanofibers entangled, and has a relatively dense morphology and a few nanopores.

[0047] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose separator with a diameter of 16 mm were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose separator on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose separator before the electrochemical performance test was performed.

[0048] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 3 The loading amounts used were 1, 3, and 9 mg / cm 2 The ultrathin cellulose separator zinc-zinc symmetric battery can perform normal charge and discharge behavior for 190, 1450, and 932 hours, with a loading of 3 mg / cm 2 The ultra-thin cellulose membrane did not short-circuit after 1450 hours, while the zinc-zinc symmetrical batteries assembled from ordinary non-woven membranes, commercial cellulose paper membranes, and commercial glass fiber membranes in Comparative Examples 1, 2, and 3 could only complete normal charge and discharge behavior for 6 hours, 2 hours, and 40 hours, respectively, before short-circuiting. 2The overpotentials of the zinc-zinc symmetric battery with ultrathin cellulose membrane during charge and discharge are 115, 107, and 132 mV, respectively. It can be seen that when the loading amount of nanocellulose fibers is too large, the dissolution and deposition overpotential of zinc will increase, which is not conducive to achieving a stable zinc negative electrode.

[0049] (4) At 5 mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 4 The loading amounts used were 1, 3, and 9 mg / cm 2 The ultra-thin cellulose membrane of the zinc-zinc symmetric battery can perform normal charge and discharge behavior for 56, 256, and 57 hours. The loading amounts of 1, 3, and 9 mg / cm 2 The overpotentials of the zinc-zinc symmetric battery with ultra-thin cellulose membrane during charge and discharge are 157, 173, and 264 mV, respectively. Similarly, the greater the loading amount of cellulose nanofibers, the greater the dissolution and deposition overpotential of zinc, which is not conducive to achieving a stable zinc negative electrode.

[0050] Example 2

[0051] Preparation of Ultrathin Cellulose Diaphragm Modified by Nano-ZnO

[0052] (1) Disperse 18.9 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) and 18.9 mg of nano zinc oxide in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL and a nano zinc oxide concentration of 0.5 mg / mL, and disperse it evenly by ultrasound. Filter the mixed dispersion onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain a hydroxycellulose nanofiber loading of 1.5 mg / cm 2 , the nano zinc oxide loading is 1.5mg / cm 2 Nano zinc oxide modified ultrathin cellulose membrane.

[0053] (2) A zinc sheet with a diameter of 10 mm and a nano-zinc oxide-modified ultra-thin cellulose separator with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the nano-zinc oxide-modified ultra-thin cellulose separator on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the nano-zinc oxide-modified ultra-thin cellulose separator before the electrochemical performance test was performed.

[0054] (3) At 5 mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 5 The zinc-zinc symmetric battery using the nano-zinc oxide modified ultra-thin cellulose membrane still did not have a short circuit after 650 hours of charge and discharge behavior, and the overpotential during the charge and discharge process was 99mV, which was better than the unmodified ultra-thin cellulose membrane in Example 1 and was more conducive to achieving a stable zinc negative electrode.

[0055] Example 3

[0056] Preparation of ultrathin cellulose membrane modified with halloysite nanotubes

[0057] (1) Disperse 18.9 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) and 18.9 mg of commercial natural halloysite nanotubes (tube outer diameter is about 50 nm, inner diameter is 15-20 nm, length is 100-1500 nm) in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL and a halloysite concentration of 0.5 mg / mL, and disperse it evenly by ultrasound. Filter the mixed dispersion onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size of 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain a hydroxycellulose nanofiber loading of 1.5 mg / cm 2 , Halloysite nanotube loading is 1.5 mg / cm 2 Halloysite nanotube-modified ultrathin cellulose separator.

[0058] (2) A zinc sheet with a diameter of 10 mm and a halloysite-modified ultra-thin cellulose membrane with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the halloysite nanotube-modified ultra-thin cellulose membrane on zinc dendrites. The electrolyte used was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the halloysite nanotube-modified ultra-thin cellulose membrane before the electrochemical performance test was performed.

[0059] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 and 5mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 6The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified with halloysite nanotubes still did not short-circuit after 1775 hours of charge and discharge behavior at a relatively low current density and cut-off capacity. The overpotential during the charge and discharge process was 52mV (the overpotential was less than and the cycle life was better than that of the unmodified ultra-thin cellulose membrane in Example 1); and at a relatively large current density and cut-off capacity (5mA / cm 2 The current density is 2.5 mAh / cm 2 The overpotential during the charge and discharge process was 62 mV (the overpotential was less than that of the unmodified ultra-thin cellulose membrane in Example 1, and the cycle life was better than that of the unmodified ultra-thin cellulose membrane in Example 1). Compared with the unmodified ultra-thin cellulose membrane in Example 1, the ultra-thin cellulose membrane modified with halloysite nanotubes is more conducive to achieving a stable zinc negative electrode.

[0060] Example 4

[0061] Preparation of Ultrathin Cellulose Diaphragm Modified with Surface Functional Layer of Copper Nanowires

[0062] (1) 12.6 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL, and 6.3 mg of copper nanowires (diameter 40-60 nm, length 0.8-6 μm) were dispersed in ethanol to prepare a dispersion with a copper nanowire concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The two dispersions were filtered onto a nylon filter membrane (model: Tianjin Jinteng microporous organic filter membrane, pore size 0.2 μm) substrate in turn by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain an ultra-thin cellulose diaphragm modified with a copper nanowire surface functional layer. Since the test uses a zinc-zinc symmetric battery, two ultra-thin cellulose diaphragms modified with a copper nanowire surface functional layer need to be stacked and used, and the copper nanowire surface functional layer side of the two diaphragms faces two zinc foils respectively to protect the zinc-zinc electrodes. Therefore, the total loading of hydroxyl cellulose nanofibers on the surface functional layer of copper nanowires modified ultrathin cellulose diaphragm is 2 mg / cm 2 , the total loading of copper nanowires is 1 mg / cm 2 , where the total loading refers to the total loading in the ultrathin cellulose membrane modified with two copper nanowire surface functional layers.

[0063] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose membrane modified with a functional layer on the surface of a copper nanowire with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery (where the functional layer surface faced the zinc negative electrode) using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose membrane modified with a functional layer on the surface of the copper nanowire on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose membrane modified with a functional layer on the surface of the copper nanowire, and then the electrochemical performance test was performed.

[0064] (3) 1 mA / cm 2 The current density is 0.5 mAh / cm 2 Cut-off capacity and 5mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 7 The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified with the copper nanowire surface functional layer did not short-circuit after 960 hours of charge and discharge behavior at a relatively low current density and cut-off capacity, and the overpotential during the charge and discharge process was 66mV (the overpotential was lower than that of the unmodified ultra-thin cellulose membrane in Example 1); and at a relatively large current density and cut-off capacity (5mA / cm 2 The current density is 2.5 mAh / cm 2 The overpotential in the charge and discharge process is 87mV (the overpotential is less than and the cycle life is better than that of the unmodified ultra-thin cellulose membrane in Example 1). Compared with the unmodified ultra-thin cellulose membrane in Example 1, the ultra-thin cellulose membrane modified with the copper nanowire surface functional layer is more conducive to achieving a stable zinc negative electrode, especially at a relatively large current density and cut-off capacity.

[0065] Example 5

[0066] Preparation of Ultrathin Cellulose Diaphragm Modified with Nano-tin Surface Functional Layer

[0067] (1) 12.6 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H2) were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL, and 6.3 mg of nanotin (particle size below 100 nm) was dispersed in ethanol to prepare a dispersion with a nanotin concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The two dispersions were filtered onto a nylon filter membrane (model: Tianjin Jinteng microporous organic filter membrane, pore size 0.2 μm) substrate in turn by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain an ultra-thin cellulose diaphragm modified with a nano-tin surface functional layer. Since the test uses a zinc-zinc symmetrical battery, two ultra-thin cellulose diaphragms modified with a nano-tin surface functional layer need to be superimposed and used, and the nano-tin surface functional layer side of the two diaphragms faces the two zinc foils respectively to protect the zinc-zinc electrodes. Therefore, the total loading of hydroxyl cellulose nanofibers on the ultra-thin cellulose membrane modified by the nano-tin surface functional layer is 2 mg / cm 2 , the total loading of nano-tin is 1 mg / cm 2 , where the total loading amount refers to the total loading amount in the ultra-thin cellulose membrane modified with two nano-tin surface functional layers.

[0068] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose membrane modified with a nano-tin surface functional layer with a diameter of 16 mm were assembled into a zinc-zinc symmetrical battery (where the functional layer surface faced the zinc negative electrode) using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose membrane modified with a nano-tin surface functional layer on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose membrane modified with a nano-tin surface functional layer before the electrochemical performance test was performed.

[0069] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetrical battery using the ultra-thin cellulose membrane with nano-tin surface functional layer still did not show short circuit after 1520 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0070] Example 6

[0071] Preparation of Ultrathin Cellulose Diaphragm Modified with Surface Functional Layer of Copper / Carbon Composite Material

[0072] (1) 12.6 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H2) were dispersed in deionized water to prepare a dispersion liquid with a hydroxycellulose nanofiber concentration of 0.5 mg / mL, 6.3 mg of copper / carbon composite material (carbon particle size is less than 500 nm, copper particle size is less than 150 nm, and copper accounts for 27% of the mass fraction of copper / carbon composite material) and 0.63 mg of cellulose nanofiber binder were dispersed in deionized water to prepare a dispersion liquid with a copper / carbon composite material concentration of 0.5 mg / mL, and the two suspensions were evenly dispersed by ultrasound. The above dispersions were filtered onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) substrate by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain a copper / carbon composite surface functional layer modified ultra-thin cellulose diaphragm. Since the test uses a zinc-zinc symmetric battery, two copper / carbon composite surface functional layer modified ultra-thin cellulose diaphragms need to be stacked and used, and the copper / carbon composite surface functional layer side of the two diaphragms faces two zinc foils respectively to protect the zinc-zinc electrodes. Therefore, the total loading of hydroxyl cellulose nanofibers in the copper / carbon composite surface functional layer modified ultra-thin cellulose diaphragm is 2mg / cm 2 The total loading of copper / carbon composite material is 1 mg / cm 2 , where the total loading refers to the total loading in the ultra-thin cellulose membrane modified by the two copper / carbon composite surface functional layers.

[0073] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose membrane modified with a copper / carbon composite surface functional layer with a diameter of 16 mm were assembled into a zinc-zinc symmetrical battery (where the functional layer surface faced the zinc negative electrode) using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose membrane modified with a copper / carbon composite surface functional layer on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose membrane modified with a copper / carbon composite surface functional layer before the electrochemical performance test was performed.

[0074] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 Cut-off capacity and 5mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Figure 8As shown. The zinc-zinc symmetrical battery using the ultra-thin cellulose diaphragm modified by the copper / carbon composite surface functional layer still did not short-circuit after 1517 hours of charge and discharge behavior at a relatively low current density and cut-off capacity, and the overpotential during charge and discharge was 51mV (the overpotential was less than and the cycle life was better than the unmodified ultra-thin cellulose diaphragm in Example 1); and after 551 hours of normal charge and discharge at a relatively large current density and cut-off capacity, there was still no short-circuit phenomenon, and the overpotential during charge and discharge was 93mV (the overpotential was less than and the cycle life was better than the unmodified cellulose diaphragm in Example 1). Compared with the unmodified ultra-thin cellulose diaphragm in Example 1, the ultra-thin cellulose diaphragm modified by the copper / carbon composite surface functional layer is more conducive to achieving a stable zinc negative electrode, especially at a relatively large current density and cut-off capacity.

[0075] Example 7

[0076] Preparation of Ultrathin Cellulose Diaphragm Modified with Candle Ash Surface Functional Layer

[0077] (1) 12.6 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H2) were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL, and 6.3 mg of candle ash (particle size 40-50 nm) were dispersed in ethanol to prepare a dispersion with a candle ash concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The two dispersions were filtered onto a nylon filter membrane (model: Tianjin Jinteng microporous organic filter membrane, pore size 0.2 μm) substrate in turn by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain an ultra-thin cellulose diaphragm modified with a candle ash surface functional layer. Since the test uses a zinc-zinc symmetrical battery, two ultra-thin cellulose diaphragms modified with a candle ash surface functional layer need to be stacked and used, and the candle ash surface functional layer side of the two diaphragms faces the two zinc foils respectively to protect the zinc-zinc electrodes. Therefore, the total loading of hydroxyl cellulose nanofibers on the candle ash surface functional layer modified ultra-thin cellulose diaphragm is 2 mg / cm 2 , the total candle ash loading is 1 mg / cm 2 , where the total loading refers to the total loading in the ultrathin cellulose membrane modified with two candle ash surface functional layers.

[0078] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose membrane with a diameter of 16 mm on the surface of candle ash functionally modified were assembled into a zinc-zinc symmetrical battery (where the functional layer surface faced the zinc negative electrode) using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose membrane with a functional layer on the surface of candle ash on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose membrane with a functional layer on the surface of candle ash, and then the electrochemical performance test was performed.

[0079] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetrical battery using the ultra-thin cellulose membrane modified with the candle ash surface functional layer still did not show short circuit after 1620 hours of charge and discharge behavior. Compared with the unmodified cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0080] Example 8

[0081] Preparation of ultrathin cellulose membrane modified with cellulose nanofiber-derived carbon surface functional layer

[0082] (1) 12.6 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL. The aforementioned commercial hydroxycellulose nanofibers were calcined in a tubular furnace at 1000°C, a hydrogen / argon mixed atmosphere (hydrogen gas volume fraction of 5%) for 1 hour, and the heating rate was 5°C / min to obtain 6.3 mg of cellulose nanofiber-derived carbon and 0.63 mg of cellulose nanofiber binder, which were dispersed in deionized water to prepare a dispersion with a cellulose nanofiber-derived carbon concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The above dispersions were filtered onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size of 0.8 μm) substrate by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain a cellulose nanofiber-derived carbon surface functionally modified ultra-thin cellulose diaphragm. Since the test uses a zinc-zinc symmetric battery, two ultra-thin cellulose membranes modified with a cellulose nanofiber-derived carbon surface functional layer need to be stacked and used, and the cellulose nanofiber-derived carbon surface functional layer side of the two membranes faces two zinc foils to protect the zinc-zinc electrodes. Therefore, the total loading of hydroxyl cellulose nanofibers on the ultra-thin cellulose membrane modified with a cellulose nanofiber-derived carbon surface functional layer is 2 mg / cm 2 , the total loading of cellulose nanofiber-derived carbon is 1 mg / cm 2, where the total loading amount refers to the total loading amount in the ultrathin cellulose membrane modified with two cellulose nano-derived carbon surface functional layers.

[0083] (2) A zinc sheet with a diameter of 10 mm and an ultra-thin cellulose membrane modified with a functional layer of cellulose nanofiber-derived carbon surface with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery (where the functional layer surface faced the zinc negative electrode) using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the ultra-thin cellulose membrane modified with a functional layer of cellulose nanofiber-derived carbon surface on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the ultra-thin cellulose membrane modified with a functional layer of cellulose nanofiber-derived carbon surface, and then the electrochemical performance test was performed.

[0084] (3) At 5 mA / cm 2 The current density is 2.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Fig. 9 The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified by the cellulose nanofiber-derived carbon surface functional layer still did not have a short circuit after 815 hours of charge and discharge behavior, and the overpotential during the charge and discharge process was 73mV (the overpotential was less than and the cycle life was better than that of the unmodified ultra-thin cellulose membrane in Example 1). Compared with the unmodified cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0085] Example 9

[0086] Preparation of Ultrathin Cellulose Diaphragm Modified by Nano-barium Titanate

[0087] (1) Disperse 25.2 mg of hydroxy cellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H1) and 12.6 mg of commercial nano barium titanate (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a particle size of less than 100 nm) in deionized water to prepare a dispersion with a cellulose nanofiber concentration of 0.5 mg / mL and a nano barium titanate concentration of 0.25 mg / mL, and disperse it evenly by ultrasound. Filter the mixed dispersion onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size of 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain a cellulose nanofiber loading of 2 mg / cm 2 , the loading amount of nano-barium titanate is 1mg / cm 2 Nano-barium titanate modified ultra-thin cellulose membrane.

[0088] (2) A zinc sheet with a diameter of 10 mm and a nano-barium titanate-modified ultra-thin cellulose membrane with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the nano-barium titanate-modified ultra-thin cellulose membrane on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the nano-barium titanate-modified ultra-thin cellulose membrane before the electrochemical performance test was performed.

[0089] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Fig.10 The zinc-zinc symmetric battery using the nano-barium titanate modified ultra-thin cellulose membrane still did not have a short circuit after 1633 hours of charge and discharge behavior, which is more conducive to achieving a stable zinc negative electrode than the unmodified ultra-thin cellulose membrane in Example 1.

[0090] Example 10

[0091] Preparation of Ultrathin Cellulose Diaphragm Modified by Nano-strontium Titanate

[0092] (1) Disperse 25.2 mg of carboxyl cellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model number TOCNF) and 12.6 mg of nano strontium titanate (particle size 40-100 nm) in deionized water to prepare a dispersion with a carboxyl cellulose nanofiber concentration of 0.5 mg / mL and a nano strontium titanate concentration of 0.25 mg / mL, and disperse it evenly by ultrasound. Filter the mixed dispersion onto a mixed cellulose water filter membrane (model number: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain a carboxyl cellulose nanofiber with a loading of 2 mg / cm 2 , nano strontium titanate loading is 1 mg / cm 2 Nano-strontium titanate modified ultrathin cellulose membrane.

[0093] (2) A zinc sheet with a diameter of 10 mm and a nano-strontium titanate-modified ultra-thin cellulose membrane with a diameter of 16 mm were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the nano-strontium titanate-modified ultra-thin cellulose membrane on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the nano-strontium titanate-modified ultra-thin cellulose membrane before the electrochemical performance test was performed.

[0094] (3) At 1 mA / cm 2The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified with nano-strontium titanate still did not show short circuit after 1825 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0095] Embodiment 11

[0096] Preparation of ultrathin cellulose membrane modified by lead titanate

[0097] (1) Disperse 25.2 mg of carboxyl cellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model number TOCNF) and 12.6 mg of lead titanate (particle size less than 1 μm) in deionized water to prepare a dispersion with a carboxyl cellulose nanofiber concentration of 0.5 mg / mL and a lead titanate concentration of 0.25 mg / mL, and disperse it evenly by ultrasound. Filter the mixed dispersion onto a mixed cellulose water filter membrane (model number: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) by vacuum filtration. Dry at room temperature for 8 hours, peel off the filter membrane substrate, and obtain a carboxyl cellulose nanofiber with a loading of 2 mg / cm 2 , lead titanate loading is 1 mg / cm 2 Lead titanate modified ultrathin cellulose separator.

[0098] (2) A zinc sheet with a diameter of 10 mm and a lead titanate-modified ultra-thin cellulose diaphragm with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the lead titanate-modified ultra-thin cellulose diaphragm on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the lead titanate-modified ultra-thin cellulose diaphragm before the electrochemical performance test was performed.

[0099] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified with lead titanate still did not show short circuit after 1652 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0100] Example 12

[0101] Preparation of Ultrathin Cellulose Diaphragm Modified by Nano-lead Zirconate

[0102] (1) Carboxylated cellulose nanofibers of model TOCNF purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd. were added to an ethanol solution with a mass fraction of 10% polyetherimide, and reacted at 30°C for 24 hours to obtain 25.2 mg of aminocellulose nanofibers and 12.6 mg of nano-lead zirconate (particle size 10-50 nm). The obtained dispersions were dispersed in deionized water to prepare a dispersion with an aminocellulose nanofiber concentration of 0.5 mg / mL and a nano-lead zirconate concentration of 0.25 mg / mL, and were evenly dispersed by ultrasound. The mixed dispersion was filtered onto a mixed cellulose water filter membrane (model: Tianjin Jinteng microporous water filter membrane, pore size 0.8 μm) by vacuum filtration. After drying at room temperature for 8 hours, the filter membrane substrate was peeled off to obtain an aminocellulose nanofiber with a loading of 2 mg / cm 2 , nano-lead zirconate loading is 1mg / cm 2 Nano-lead zirconate modified ultra-thin cellulose separator.

[0103] (2) A zinc sheet with a diameter of 10 mm and a nano-lead zirconate-modified ultra-thin cellulose diaphragm with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the nano-lead zirconate-modified ultra-thin cellulose diaphragm on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the nano-lead zirconate-modified ultra-thin cellulose diaphragm before the electrochemical performance test was performed.

[0104] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetric battery using the ultra-thin cellulose membrane modified with nano-lead zirconate still did not show short circuit after 1536 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0105] Embodiment 13

[0106] Preparation of ultrathin cellulose membrane modified with polyvinylidene fluoride

[0107] (1) 25.2 mg of carboxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model number TOCNF) were dispersed in deionized water to prepare a dispersion with a concentration of 0.5 mg / mL of carboxycellulose nanofibers. 12.6 mg of polyvinylidene fluoride (average weight-average molecular weight 400,000) was dispersed in ethanol to prepare a dispersion with a polyvinylidene fluoride concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The two dispersions were filtered onto a nylon filter membrane (model number: Tianjin Jinteng microporous organic filter membrane, pore size 0.2 μm) substrate in turn by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain a carboxycellulose nanofiber with a loading of 2 mg / cm 2 , polyvinylidene fluoride loading is 1mg / cm 2 Polyvinylidene fluoride modified ultra-thin cellulose membrane.

[0108] (2) A zinc sheet with a diameter of 10 mm and a polyvinylidene fluoride modified ultra-thin cellulose membrane with a diameter of 16 mm were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the polyvinylidene fluoride modified ultra-thin cellulose membrane on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the polyvinylidene fluoride modified ultra-thin cellulose membrane before the electrochemical performance test was performed.

[0109] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetrical battery using the ultra-thin cellulose membrane modified with polyvinylidene fluoride still did not show short circuit after 1687 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0110] Embodiment 14

[0111] Preparation of Ultrathin Cellulose Separator Modified with Polyethylene Oxide

[0112] (1) 25.2 mg of hydroxycellulose nanofibers (purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., model CNF-H2) were dispersed in deionized water to prepare a dispersion with a hydroxycellulose nanofiber concentration of 0.5 mg / mL. 12.6 mg of polyethylene oxide (average viscosity-average molecular weight 2000000) was dispersed in ethanol to prepare a dispersion with a polyethylene oxide concentration of 0.5 mg / mL. The two suspensions were evenly dispersed by ultrasound. The two dispersions were filtered onto a nylon filter membrane (model: Tianjin Jinteng microporous organic filter membrane, pore size 0.2 μm) substrate in turn by vacuum filtration, dried at room temperature for 8 hours, and the filter membrane substrate was peeled off to obtain a hydroxycellulose nanofiber loading of 2 mg / cm 2 , polyethylene oxide loading is 1 mg / cm 2 Polyethylene oxide modified ultrathin cellulose membrane.

[0113] (2) A zinc sheet with a diameter of 10 mm and a polyethylene oxide-modified ultra-thin cellulose membrane with a diameter of 16 mm were assembled into a zinc-zinc symmetric battery using a CR2032 button battery shell for electrochemical performance testing to explore the inhibitory effect of the polyethylene oxide-modified ultra-thin cellulose membrane on zinc dendrites. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the polyethylene oxide-modified ultra-thin cellulose membrane before the electrochemical performance test was performed.

[0114] (3) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity was used as the test condition for constant current charge and discharge test. The zinc-zinc symmetric battery using the polyethylene oxide modified ultra-thin cellulose membrane still did not show short circuit after 1468 hours of charge and discharge behavior. Compared with the unmodified ultra-thin cellulose membrane in Example 1, it is more conducive to achieving a stable zinc negative electrode.

[0115] Comparative Example 1

[0116] (1) A zinc sheet with a diameter of 10 mm punched out by a punching machine and a non-woven fabric separator with a diameter of 16 mm (thickness of 200 μm, pore size of 10-200 μm) were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing. The electrolyte used was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the non-woven fabric separator, and then the electrochemical performance test was performed.

[0117] (2) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Fig.11 As shown in Figure 2, the zinc-zinc symmetric battery using non-woven fabric as a separator experienced a short circuit after 6 hours of charge and discharge.

[0118] Comparative Example 2

[0119] (1) A zinc sheet with a diameter of 10 mm punched out by a punching machine and a commercial cellulose paper separator with a diameter of 16 mm (manufactured by Mitsubishi, Japan, with a thickness of 36 μm and a pore size of 0.5-2 μm) were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left standing at room temperature for 6 hours to allow the electrolyte to fully infiltrate the non-woven fabric separator, and then the electrochemical performance test was performed.

[0120] (2) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Fig.12 As shown in Figure 2, a zinc-zinc symmetric battery using commercial cellulose paper as a separator experienced a short circuit after 2 hours of charge and discharge.

[0121] Comparative Example 3

[0122] (1) A zinc sheet with a diameter of 10 mm punched out by a punching machine and a glass fiber separator with a diameter of 16 mm (model: Whatman GF / A, thickness: 260 μm, pore size: about 1-100 μm) were assembled into a zinc-zinc symmetrical battery using a CR2032 button battery shell for electrochemical performance testing. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The assembled battery was left to stand at room temperature for 6 hours to allow the electrolyte to fully infiltrate the commercial glass fiber separator, and then the electrochemical performance test was performed.

[0123] (2) At 1 mA / cm 2 The current density is 0.5 mAh / cm 2 The cut-off capacity is used as the test condition for constant current charge and discharge test. The charge and discharge curve is as follows Fig.13 As shown in Figure 2, a zinc-zinc symmetric battery using commercial glass fiber as a separator experienced a short circuit after 40 hours of charge and discharge.

[0124] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a modified ultra-thin cellulose membrane, characterized in that The following steps are involved: (1) Dispersing cellulose nanofibers uniformly in water to obtain a cellulose aqueous suspension; dispersing the functional material in a solvent to obtain a suspension 2; (2) This step is the following step (2.1) or step (2.2): (2.1) blending the aqueous cellulose suspension and the suspension 2, and then filtering the mixture onto a filter membrane substrate. After drying at room temperature, the filter membrane substrate is peeled off to obtain a modified ultrathin cellulose membrane. Alternatively, (2.2) filtering the aqueous cellulose suspension onto a filter membrane substrate to obtain an ultra-thin cellulose membrane matrix, and then filtering the suspension 2 onto the obtained ultra-thin cellulose membrane matrix to obtain a modified ultra-thin cellulose membrane; The functional material in step (1) includes one of halloysite nanotubes, nano-lead zirconate, and polyvinylidene fluoride; The cellulose nanofibers described in step (1) contain at least one of carboxyl, hydroxyl, and amino functional groups; The thickness of the modified ultra-thin cellulose membrane is 5-40 μm.

2. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: The cellulose nanofibers described in step (1) have a diameter of 5-200 nm and a length of 0.5-20 µm.

3. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: The solvent used to disperse the functional material in step (1) is one of water, an organic solvent or a water / organic solvent mixture; The amounts of the functional material and the solvent in step (1) satisfy: the concentration of the functional material in the solvent is 0.05-10 mg / mL; The concentration of the cellulose aqueous suspension in step (1) is 0.5-1 mg / mL.

4. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: The amount of the cellulose aqueous suspension and the suspension 2 in step (2.1) and step (2.2) is such that the loading amount of the cellulose nanofibers is 0.5-10 mg / cm 2 The loading amount of the functional material is 0.1-9 mg / cm 2 ; The mass fraction of the functional material in the modified ultra-thin cellulose membrane is 0-90%.

5. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: The amount of the cellulose aqueous suspension and the suspension 2 in step (2.1) and step (2.2) is such that the loading amount of the cellulose nanofibers is 1-6 mg / cm 2 The loading amount of the functional material is 0.3-5 mg / cm 2 ; The mass fraction of the functional material in the modified ultra-thin cellulose membrane is 5%-50%.

6. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: A certain proportion of cellulose nanofibers is mixed into the suspension 2 in step (2.2) to act as a binder, wherein the mass percentage of the mixed cellulose nanofibers in the functional material is 0-20%.

7. The method for preparing a modified ultra-thin cellulose separator according to claim 1, characterized in that: The filter membrane substrates described in step (2.1) and step (2.2) are mixed cellulose water filter membranes or nylon filter membranes with a pore size of 0.01-2 µm; the mixed cellulose water filter membranes are suitable for the case where the solvent in step (1) is water, and the nylon filter membranes are suitable for the case where the solvent in step (1) is an organic solvent or water or a mixture of the two.

8. A modified ultra-thin cellulose separator prepared according to the method according to any one of claims 1 to 7.

9. Use of the modified ultra-thin cellulose membrane according to claim 8 in an aqueous zinc-based energy storage system.

10. An aqueous zinc-based energy storage system, characterized in that it comprises the modified ultra-thin cellulose membrane according to claim 8.

Citation Information

Patent Citations

  • Zinc ion battery diaphragm for inhibiting zinc dendrites, and preparation method thereof

    CN112332026A

  • Separator modifying method for zinc negative electrode battery

    CN109920956A

  • Cellulose diaphragm suitable for zinc ion battery and application thereof

    CN112615106A

  • Cellulose-based diaphragm, and preparation method and application thereof

    CN113224463A

  • Preparation method of bacterial cellulose-based aqueous zinc ion battery diaphragm material

    CN113270686A